Pemberdayaan Masyarakat melalui Wisata Religi Maqom Dewi Amirah Kencono Wungu di Desa Nambangrejo Kec Sukorejo Ponorogo - Ilhami, Azhar Hari; Nafiah, Tsalits Maratun (Institut Agama Islam Sunan Giri Ponorogo, 2024)
Abstract Religious tourism has its own charm Religious tourism has its own charm for tourists with spiritual values and can increase our knowledge of the history or origin of the place that is sacred and designated as religious tourism. The development of religious tourism objects has a broad economic driving force, not solely related to the increase in tourist visits, but more importantly is the development of tourism that is able to build a person's national spirit, and further enhance our worship of the Creator. The development of religious tourism objects in Indonesia has not run optimally, even though this aspect is very influential in improving the community's economy, especially local revenue. How is the community empowerment strategy through the existence of Dewi Amirah Tomb in Nambangrejo Village, Sukorejo District, Ponorogo Regency. What are the inhibiting and supporting factors for the community empowerment strategy through the existence of Dewi Amirah's Tomb in Nambangrejo Village, Sukorejo District, Ponorogo Regency. This research was conducted qualitatively using a case study approach to find out how the community empowerment strategy through the existence of Dewi Amirah's Tomb in Nambangrejo Village, Sukorejo District, Ponorogo Regency with data collection procedures through observation, interview, and documentation techniques. The data obtained is then analyzed to systematically search and organize the records of observations, interviews, and documentation about the case under study. Based on the results of data analysis, it is concluded that the community empowerment strategy through the existence of the Tomb of Dewi Amirah in Nambang Rejo Village, Sukorejo District, Ponorogo Regency is classified as good and successful, there are several supporting and inhibiting factors for the community empowerment strategy through the existence of the Tomb of Dewi Amirah in Nambangrejo Village, Sukorejo District, Ponorogo Regency.